2021
DOI: 10.1021/jacs.1c02442
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Chromophore States in a Reversibly Switchable Green Fluorescent Protein: Mechanistic Insights from NMR Spectroscopy

Abstract: The photophysical properties of fluorescent proteins, including phototransformable variants used in advanced microscopy applications, are influenced by the environmental conditions in which they are expressed and used. Rational design of improved fluorescent protein markers requires a better understanding of these environmental effects. We demonstrate here that solution NMR spectroscopy can detect subtle changes in the chemical structure, conformation, and dynamics of the photoactive chromophore moiety with at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…When studying a closely related protein rsFolder, Cristou et al 12 concluded that solvent protons can easily migrate to the chromophore-containing pocket and protonate the hydroxybenzylidene ring of the chromophore "on a submilliseconds time scale". In line with this finding, which presumably holds for rsEGFP2 as well, the following equilibrium is addressed by our models of the ON-state (A-cis)  + H +  (N-cis)  (Eq.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When studying a closely related protein rsFolder, Cristou et al 12 concluded that solvent protons can easily migrate to the chromophore-containing pocket and protonate the hydroxybenzylidene ring of the chromophore "on a submilliseconds time scale". In line with this finding, which presumably holds for rsEGFP2 as well, the following equilibrium is addressed by our models of the ON-state (A-cis)  + H +  (N-cis)  (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…5 The Chro protonation state alteration as well as of the surrounding Chro molecular groups was also put forward by studies of the OFF → ON transformations of rsEGFP2. 7,8 When discussing protonation in rsEGFP2, we note the very recent paper 12 that reports results of the NMR studies for a related GFP-like reversibly switchable protein rsFolder with the same composition of the chromophore and only few variations in amino acid residues neighboring to the chromophore. 6 The obtained data show that the relative population of the chromophore ON-and OFFstates vary in a complex pH-dependent manner.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 The Chro protonation state alteration as well as of the surrounding Chro molecular groups was also put forward by studies of the OFF → ON transformations of rsEGFP2. 7,8 When discussing protonation in rsEGFP2, we note the very recent paper 12 that reports results of the NMR studies for a related GFP-like reversibly switchable protein rsFolder with the same composition of the chromophore and only few variations in amino acid residues neighboring to the chromophore. 6 The obtained data show that the relative population of the chromophore ON-and OFFstates vary in a complex pH-dependent manner.…”
Section: Introductionmentioning
confidence: 99%